2015
DOI: 10.1021/jacs.5b04767
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Biological Investigation of (−)-Promysalin

Abstract: Compounds that specifically target pathogenic bacteria are greatly needed, and identifying the method by which they act would provide new avenues of treatment. Herein we report the concise, high-yielding total synthesis (eight steps, 35% yield) of promysalin, a natural product that displays antivirulence phenotypes against pathogenic bacteria. Guided by bioinformatics, four diastereomers were synthesized, and the relative and absolute stereochemistries were confirmed by spectral and biological analysis. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 27 publications
1
53
0
5
Order By: Relevance
“…281 Genomic analysis of the biosynthetic cluster proposed by De Mot indicated that the natural L-proline is incorporated into the natural product; the remaining stereocenters were both in the myristate side chain. This synthetic approach featured a convergent strategy in which precursors each containing one stereocenter were joined through cross-metathesis, permitting straightforward preparation of the various diastereomers.…”
Section: Narrow-spectrum Small Molecule Natural Productsmentioning
confidence: 99%
“…281 Genomic analysis of the biosynthetic cluster proposed by De Mot indicated that the natural L-proline is incorporated into the natural product; the remaining stereocenters were both in the myristate side chain. This synthetic approach featured a convergent strategy in which precursors each containing one stereocenter were joined through cross-metathesis, permitting straightforward preparation of the various diastereomers.…”
Section: Narrow-spectrum Small Molecule Natural Productsmentioning
confidence: 99%
“…Moreover,i ta lso kills persister cells effectively without showing toxicity to mammalian cells. [254] Moreover, these compounds do not cause damage to human cells.…”
Section: Biofilm Inhibitorsmentioning
confidence: 99%
“…Kürzlich wurden kationische Pillararene (Abbildung 17) als Biofilm-Inhibitoren nachgewiesen, welche die Bildung des Biofilms bei sub-MIC-Konzentrationen in verschiedenen, klinisch relevanten Gram-positiven Pathogenen, einschließlich S. aureus und E. faecalis verhindern. [254] [249] Zusätzlich zu synthetischen Molekülen gibt es in der Natur eine Vielzahl an niedermolekularen Substanzen, die auf die Bekämpfung der Biofilm-Bildung zugeschnitten sind.…”
Section: Angewandte Chemieunclassified